Meningkatkan Kemampuan Motorik Halus Anak melalui Kegiatan Menulis di Atas Pasir - Tiara Erlianda; Ahmad Fauzi; Khairul Amri (Aṭfāluna: Journal of Islamic Early Childhood Education, 2019)
The fine motor skills of children in the group B2 of TK Islam Terpadu Darul Mukhlishin are still lack. It can be seen from the results of the letters written by the child that is not in accordance with the example given by the teacher. The study aims to an increase in children’s fine motor skills through writing activities on the sand in TK Islam Terpadu Darul Mukhlishin. This type of research is a classroom action research conducted in 2 cycles. This research uses a quantitative approach with descriptive statistical methods. Data collection techniques used were observation, interview and tests. The research instrument used observation sheets, interview sheets and tests. Data analysis techniques used descriptive and inferential statistics using t-test. The results showed that fine motor skills achieved by children in group B2 before the action reached 30.25%. In the first cycle of action reached 61.125% while in the second cycle of action reached 91.5%. In testing hypotheses through t-test with a significant level of 5%, it show that the value of t-count ≥ t-table is 22.23 ≥ 2.093, it can be concluded that H0 is rejected and Ha is accepted, namely writing on sand can improve children’s fine motor skills in group B2 of TK Islam Terpadu Darul Mukhlishin.